(-3+2-1)³-(-3+5-1)⁸+3
![( - 3 + 2 - 1) - ( - 3 + 5 - 1)^{8} + 3 ( - 3 + 2 - 1) - ( - 3 + 5 - 1)^{8} + 3](https://tex.z-dn.net/?f=%28+-+3+%2B+2+-+1%29+-+%28+-+3+%2B+5+-+1%29%5E%7B8%7D++%2B+3)
Soluções para a tarefa
Respondido por
0
Explicação passo-a-passo:
(-4+2)³ - ( -4+5)⁸ +3=
( - 2)³ - ( +1)⁸ +3=
- 8 - (+1) +3=
- 8 - 1 +3=
- 9 +3=
- 6
Perguntas interessantes
Química,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
7 meses atrás
Espanhol,
7 meses atrás
Matemática,
7 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás